Alumina-graphene nanocomposite coatings fabricated by suspension high velocity oxy-fuel thermal spraying for ultra-low-wear - Murray, James W.; Rance, Graham A.; Xu, Fang; Hussain, Tanvir (Elsevier, 2017)
An alumina coating containing 1 wt.% graphene nanoplatelets (GNPs) is deposited for the first time by suspension high velocity oxy-fuel (SHVOF) thermal spraying – an emerging coating deposition technique. Raman spectroscopy shows the GNPs survive the process albeit with a two-fold increase in the density of defects in the graphitic lattice. Dry-sliding wear testing at a 10 N load yields a two order of magnitude reduction in the specific wear rate for the alumina/GNP composite in comparison to the equivalent pure alumina coating. Testing with varying loads shows that the transition to the severe wear regime is prevented until between 30 and 35 N for the alumina + GNP coating which otherwise occurs between 5 and 7.5 N in the absence of GNPs. A reinforced microstructure, and specifically fracture toughness, explains the improved wear behaviour as opposed to tribofilm formation.